2016
DOI: 10.1186/s13018-016-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of morphological variations of the cortical wall at the bone-cement interface

Abstract: BackgroundThe integrity of bone-cement interface is very important for the stabilization and long-term sustain of cemented prosthesis. Variations in the bone-cement interface morphology may affect the mechanical response of the shape-closed interlock.MethodsSelf-developed new reamer was used to process fresh pig reamed femoral canal, creating cortical grooves in the canal wall of experimental group. The biomechanical effects of varying the morphology with grooves of the bone-cement interface were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Similar findings have been demonstrated at various times in connection with bone cement. In cemented implants, failure almost always occurs at the cement–bone interface, and it has been shown that failure strength increases with increasing contact area of the bone and cement.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been demonstrated at various times in connection with bone cement. In cemented implants, failure almost always occurs at the cement–bone interface, and it has been shown that failure strength increases with increasing contact area of the bone and cement.…”
Section: Discussionmentioning
confidence: 99%